Antibody–Prodrug Conjugates with KSP Inhibitors and Legumain‐Mediated Metabolite Formation. Issue 35 (3rd May 2019) - Lerchen, Hans‐Georg; Stelte‐Ludwig, Beatrix; Berndt, Sandra; Sommer, Anette; Dietz, Lisa; Rebstock, Anne‐Sophie; Johannes, Sarah; Marx, Leo; Jörißen, Hannah; Mahlert, Christoph; Greven, Simone
Abstract: Invited for the cover of this issue is the group of Hans‐Georg Lerchen and colleagues from Bayer AG R&D Pharmaceuticals. The image, provided by J. Franz and graphic designers from The New Atlantic (Cologne), depicts a cartoon representation of the legumain‐mediated cleavage of the peptide cap within the lysosome. Read the full text of the article at 10.1002/chem.201900441 . Abstract : " The use of legumain‐cleavable caps as demonstrated here for antibody‐prodrug conjugates (APDCs) holds promise in applying it to different types of solid tumor indications to improve the therapeutic window ." Read more about the story behind the cover in the Cover Profile and about the research itself on page 8208 ff. (DOI: 10.1002/chem.201900441 ).